Das deutsch-ungarische Volksgruppenabkommen von 1940 als Ausdruck des NS-Volksgruppenrechts - Albrecht, Timo Marcel (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2022)
This article analyses the 1940 German-Hungarian “Volksgruppenabkommen” (National Minority Agreement) of Vienna and seeks to answer the question whether it forms an expression of the national socialist concept of Volksgruppenrecht (i.e. the “völkisch” version of national minority law). In the Agreement Hungary granted far-reaching autonomy rights to its German minority. This happened parallel to Germany’s and Italy’s support for a partial border revision for the benefit of Horthy’s Hungary in the Second Vienna Award (“Vienna Diktat”) and due to strong political pressure by the Reich. National socialist academia celebrated the Agreement as a milestone for the German plans with regard to the sphere (“Raum”) of South-East Europe. After providing a historic contextualization and an overview of the Agreement in general, core academic elements of the minority law during the Nazi period (1933–1945) are introduced. By comparing the Agreement with key ideas of Ns Volksgruppen law, the article argues that both are strongly interconnected and the Agreement indeed codifies core concepts of the latter.